Examining the Intersection of Race, Gender, Class, and Age on Post-Secondary Education and Career Trajectories of Refugees - Bajwa, Jaswant Kaur; Abai, Mulugeta; Kidd, Sean; Couto, Sidonia; Akbari-Dibavar, Aytak; McKenzie, Kwame (Refuge)

(untitled) (Centre for Refugee Studies, York University, 2018)
This study examines the role of demographics on education and career trajectories of refugees’ in Canada from an intersectional perspective. It implemented a 14-week unique educational program that was completed by a total of 41 refugees’, over two cohorts with the goal to overcome barriers, bridge gaps and facilitate their transition into higher education. The data collected using semi-structured interview guide was analyzed using a constant comparative method. The findings suggest that a supportive educational model that promotes safety, sense of belonging and empowerment are critical to combat the structural racism, sexism and other discriminatory factors in accessing higher education.